2022
DOI: 10.2478/rir-2022-0031
|View full text |Cite
|
Sign up to set email alerts
|

Social media for research discourse, dissemination, and collaboration in rheumatology

Abstract: Social media has become an important venue for rheumatologists, patients, organizations, and other stakeholders to discuss recent research advances in diagnosis and management of rheumatic disorders. In this article, we describe the current state of how social media may enhance dissemination, discourse, and collaboration in rheumatology research. Social media may refer to social platforms like Twitter and Instagram or digital media like podcasts and other websites that are operated for providing as free, open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…FCPs reported being most likely to engage with tweets containing prepackaged knowledge and salient points of research evidence. This aligns with the emergence of knowledge translation tools such as actionable nuggets [ 28 ] and clinical knowledge summaries [ 29 ] and recent commentary discussing how Tweetorials (a collection of tweets that aim at educating users who engage with them) and tweet threads (a series of connected posts from one person) are useful to keep up to date with research findings [ 30 ]. Visual posts were reported by participants as being most engaging, aligning with a 2019 systematic review that found that health care professionals believe infographics reduce the time burden of reading full texts [ 31 ].…”
Section: Discussionmentioning
confidence: 74%
“…FCPs reported being most likely to engage with tweets containing prepackaged knowledge and salient points of research evidence. This aligns with the emergence of knowledge translation tools such as actionable nuggets [ 28 ] and clinical knowledge summaries [ 29 ] and recent commentary discussing how Tweetorials (a collection of tweets that aim at educating users who engage with them) and tweet threads (a series of connected posts from one person) are useful to keep up to date with research findings [ 30 ]. Visual posts were reported by participants as being most engaging, aligning with a 2019 systematic review that found that health care professionals believe infographics reduce the time burden of reading full texts [ 31 ].…”
Section: Discussionmentioning
confidence: 74%
“…The pandemic also provided an opportunity to demonstrate the potential power of social media to facilitate, conduct, and disseminate research. 49 Nearly simultaneous with the onset of the pandemic was the formation of the GRA, an international collaboration designed to investigate outcomes of patients with rheumatic disease during the pandemic. 50 Although the pandemic limited research opportunities for many investigators, avenues to new research were opened regarding outcomes of patients with rheumatic disease who were infected with COVID-19 as well as their response to vaccination and prophylactic monoclonal antibody therapy.…”
Section: Research Opportunitiesmentioning
confidence: 99%
“…The pandemic also provided an opportunity to demonstrate the potential power of social media to facilitate, conduct, and disseminate research 49 . Nearly simultaneous with the onset of the pandemic was the formation of the GRA, an international collaboration designed to investigate outcomes of patients with rheumatic disease during the pandemic 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Coler-Reilly et al . [ 7 ] present a narrative review on social media for research discourse, dissemination, and collaboration focused on rheumatology. They describe how many social platforms, especially Twitter, can facilitate research collaboration, clinician education, and patient engagement.…”
mentioning
confidence: 99%